Why do many translators resist post-editing? A sociological analysis using Bourdieu's concepts - Akiko Sakamoto (JoSTrans: The Journal of Specialised Translation)
More and more language service providers (LSPs) are now using a post-edited machine translation (PEMT) production model in addition to, or instead of, the traditional Translation-Editing-Proofreading (TEP) model, in order to cope with the growing demand for translation. As a result, translators are increasingly expected to work as post-editors in the PEMT process, but the reluctance of translators or resistance to this expectation is evident as they feel their professional skills and identities are sidelined by technology (Kelly 2014; Cadwell et al. 2017). This article attempts to provide a theoretical description of the translators' resistance to post-editing work using Bourdieu's concepts: capital, field and habitus. Bourdieu's sociological framework allows us to examine the positions of translators and post-editors in the field of translation and its mechanism of emotional impacts. For this purpose, I draw on qualitative and quantitative data collected in a focus group study with 16 UK translation project managers, a survey of 155 company websites and two training manuals for post-editors. The study will provide industry stakeholders, as well as translation educators, useful conceptualisation tools to understand the current situation surrounding social agency of translators and post-editors.